2020
DOI: 10.1002/hed.26557
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory thyroidectomy is safe and beneficial in papillary thyroid carcinoma: Randomized controlled trial

Abstract: Background: Currently, no randomized controlled trial has been performed to investigate the safety profiles, economic benefit and mental health of ambulatory thyroidectomy in patients with papillary thyroid carcinoma (PTC). Methods: Patients diagnosed with PTC were enrolled in this study and were randomly assigned to ambulatory group and control group. The safety profiles, economic benefit and mental health were investigated. Results: Four hundred and eleven patients completed the study. There was no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Meantime, the present study also showed significant economic benefits and a shorter duration of hospitalization in ambulatory ETCBA, which was solid but not surprising because the ambulatory management was administrated to achieve these purposes. Additionally, multiple studies on ambulatory surgery reported similar patient benefits (7,(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Meantime, the present study also showed significant economic benefits and a shorter duration of hospitalization in ambulatory ETCBA, which was solid but not surprising because the ambulatory management was administrated to achieve these purposes. Additionally, multiple studies on ambulatory surgery reported similar patient benefits (7,(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, the mental health of patients was also investigated within one month, using the Depression Anxiety Stress Scales-21 (DASS-21), a screening tool to measure three comorbid depression, anxiety and stress disorders (Supplement Table 1) (7).…”
Section: Outcomes and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomised controlled trials and large multicentre studies (e.g., population-based studies) are required to ensure the best evidence supports these results. Zhang et al [ 50 ] recently published an RCT on outpatient total and hemithyroidectomy reporting that outpatient thyroidectomy is safe in patients with papillary thyroid carcinoma. This RCT was not relevant in this review as the outpatient setting described was discharge before 23 h. Completing an RCT that examines the risk of PTB in a selected outpatient population is challenging as the PTB outcome is so rare.…”
Section: Discussionmentioning
confidence: 99%
“…Os impactos da tireoidectomia vêm melhorando com os anos (3) , mas além dos aspectos funcionais pode haver impacto negativo na qualidade de vida em voz, com redução no pré operatório (2,6) , e alterações emocionais (3,(8)(9)(10) associadas ao diagnóstico dos nódulos tireoidianos.…”
Section: Introductionunclassified